2001
DOI: 10.1128/aac.45.5.1360-1366.2001
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Activities of Aminoadamantane and Aminoalkylcyclohexane Derivatives against Trypanosoma brucei

Abstract: We reported recently that the bloodstream form of the African trypanosome, Trypanosoma brucei, is sensitive to the anti-influenza virus drug rimantadine. In the present report we describe the trypanocidal properties of a further 62 aminoadamantane and aminoalkylcyclohexane derivatives. Seventeen of the compounds were found to be more active than rimantadine, with four inhibiting growth in vitro of T. brucei by >90% at concentrations of 1 M. The most active derivative (1-adamantyl-4-amino-cyclohexane) was about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 24 publications
2
24
0
5
Order By: Relevance
“…In a follow-up study, a larger compound library of 62 aminoadamantane- and aminocyclohexane derivatives was screened against T. brucei in an in vitro assay. 356 Of the screened compounds, 17 were more active than rimantadine, some of which are depicted in Scheme 28. Increased hyrophobicity obviously enhances trypanocidal activity, and compound 188 was the most potent screened, being about 20–25 times more effective than rimantadine.…”
Section: The First Hit: Adamantane Derivatives As Antivirals and Amentioning
confidence: 99%
“…In a follow-up study, a larger compound library of 62 aminoadamantane- and aminocyclohexane derivatives was screened against T. brucei in an in vitro assay. 356 Of the screened compounds, 17 were more active than rimantadine, some of which are depicted in Scheme 28. Increased hyrophobicity obviously enhances trypanocidal activity, and compound 188 was the most potent screened, being about 20–25 times more effective than rimantadine.…”
Section: The First Hit: Adamantane Derivatives As Antivirals and Amentioning
confidence: 99%
“…We evaluated their antifungal and anti-trypanosome activity, and the results suggest a more pronounced activity for 2,3-DMeB relative to 3,4-DMeB. Antifungal and anti-trypanosomal activity had already been demonstrated for guanylhydrazones [37,39,40]. Santos-Filho et al [38] suggested that the action mechanism for guanylhydrazone derivatives may include three different pathways: (a) interaction with the membranes of the organism, which are negatively charged; (b) interaction with some specific enzyme of the organism; and (c) interaction with the DNA of the organism.…”
Section: Discussionmentioning
confidence: 95%
“…The combination of dendritic materials possessing an adamantane core, which has significant potential in biomedical applications , with the physical characteristics of inorganic montomorillonite clay, such as Nanofil, is anticipated to generate novel utilitarian composites. Toward this goal, the N ‐[[[2‐Hydroxy‐l,l‐bis(hydroxymethyl)ethyl]amino]carbonyl]adamantane (Adm), possessing three hydroxyl termini, was prepared .…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the resulting Adm‐p‐MMA‐b‐gly/NC contained adamantane core, as a new functionality. Adamantane is a cage‐type hydrocarbon that has pharmaceutical significance, where its derivatives are used as antiviral agents in the treatment of various diseases . It is also highly thermally stable; therefore, incorporation of the adamantane moiety and glucose unit in the desired nanocomposites by using chitosan‐modified clay, as a nanofiller, was expected to create temperature‐resistant materials for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%